Factor-target analysis of multi-target control of brewing technological complex functioning - Романов, Микола Сергійович; Кишенько, Василь Дмитрович; Ладанюк, Анатолій Петрович (Technology audit and production reserves, 2015)
The work is devoted to the issue of optimization of basic technological processes in beer production. A causal-target and factor-target analysis of the technological complex of the brewery was made, taking into account the mutual influence of the individual processes. We used the methods of factor analysis and cognitive modeling, which allowed to determine the set of attributes, flows, factors, life conditions of the brewery as an object of control and to form the structure of interaction between objects and factors. Factor-target analysis of the system was implemented on the basis of the expert survey using multidimensional scaling method for the further development of the scenario control system of technological complex of the brewery. Causal-target and factor-target diagrams for the process of brewing are given. The studies will help to better define the primary and secondary factors affecting the quality of the final product and resources usage. Scenario control system of beer making process will be established on the basis of the obtained data.